Hit Identification of a Novel Dual Binder for h‐telo/c‐myc G‐Quadruplex by a Combination of Pharmacophore Structure‐Based Virtual Screening and Docking Refinement. (23rd March 2016) - Rocca, Roberta; Costa, Giosuè; Artese, Anna; Parrotta, Lucia; Ortuso, Francesco; Maccioni, Elias; Pinato, Odra; Greco, Maria Laura; Sissi, Claudia; Alcaro, Stefano; Distinto, Simona; Moraca, Federica
Abstract: It is well known that G‐quadruplexes are targets of great interest for their roles in crucial biological processes, such as aging and cancer. Hence, a promising strategy for anticancer drug therapy is the stabilization of these structures by small molecules. We report a high‐throughput in silico screening of commercial libraries from several different vendors by means of a combined structure‐based pharmacophore model approach followed by docking simulations. The compounds selected by the virtual screening procedure were then tested for their ability to interact with human telomeric G‐quadruplex folding by circular dichroism, fluorescence spectroscopy, and fluorescence intercalator displacement. Our approach resulted in the identification of a 13‐[(dimethylamino)methyl]‐12‐hydroxy‐8 H ‐benzo[ c ]indolo[3, 2, 1‐ ij ][1, 5]naphthyridin‐8‐one derivative as a novel promising stabilizer of G‐quadruplex structures within the human telomeric and the c‐myc promoter sequences. Abstract : Pushing through : A high‐throughput in silico screening of libraries by a structure‐based pharmacophore model approach was undertaken. Docking simulations and biophysical tests of selected compounds were carried out to determine their capacity to interact with the human telomeric G‐quadruplex (G4). Hit56, a 13‐[(dimethylamino)methyl]‐12‐hydroxy‐8 H ‐benzo[ c ]indolo[3, 2, 1‐ ij ][1, 5]naphthyridin‐8‐one derivative, was identified as a promising stabilizer of G4 structures.